Ny produktionslayout för bättre internlogistik på Ewes 3 - Johnsson, Andreas (My University, 2020)
This thesis is done at Ewes Stålfjäder AB in Bredaryd which manufactures spring solutions and environmental products. The last couple of years increased demand on environmental products have led to suffering internal logistics. The assignment has been to study the flow of material at the department Ewes 3, with focus on manufacturing of welded wire cages, identify problems and develop a layout proposition. To make a situation assessment, data collection where made from the company’s business system, interviews and observations. The analysis is done with assistance from the process flow diagram and layout flow chart which led to the requirements and factors of valuation used in development of layout propositions. The most significant factors to meet the demands on specific products from the customers is flexibility and flow of material. Five different layouts where generated through the method of simplified systematic local planning and weighted in a chart. The winning alternative excelled in utilizing the buildings properties, e.g. creating a new gate. A legible dividing is made for the two product families at the department. Separated flows makes for easier internal transports. While at the same time, creating area for handling, storage and future expansion of machine capacity. The chosen proposition is only a minor part in a necessary work of improvement towards a rational production. At the company, there are several other production- and organization aspects that needs to be considered, like storage management, reduction of machine changeovers and standardizing of work procedures, semi-manufactured articles and products.